Inside Back Cover: Gold‐Catalyzed C−H Functionalization Polycondensation for the Synthesis of Aromatic Polymers (Angew. Chem. Int. Ed. 49/2020). Issue 49 (19th October 2020) - King, Eric R.; Tropp, Joshua; Eedugurala, Naresh; Gonce, Lauren E.; Stanciu, Sonia; Azoulay, Jason D.
Abstract : Gold‐catalyzed polymerization reactions enable the synthesis of novel aromatic polymers. In their Communication on page 21971, J. D. Azoulay and co‐workers demonstrate how the multifaceted reactivity of cationic gold promotes direct C−H functionalization polycondensations between alkyne‐containing comonomers and the C(sp 2 )−H bonds of diverse heteroarenes. The high reactivities and exceptional degrees of polymerization afford a valuable approach to polymerize a veritable treasure trove of otherwise unreactive monomers.